MODERN WORLD PICTURE IN THE DIALOGUE OF SCIENCE AND RELIGION: CONCEPTUAL IDEAS AND METHODOLOGIES - Shashkova, Liudmyla (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The subject of the connection between science and religion is a a prominent trend in contemporary philosophy of science. The prerequisites of the study are the conceptual and methodological foundations for dialogue between science and religion concerning fundamental problems of the contemporary world picture. The aim and tasks. Focusing on the analysis of the relationship between science and religion from the standpoint of the social philosophy of science, the study aims to represent a dialogical turn in the modern context. Research methods. The methodological basis of the study are the strategies and approaches of the social philosophy of science. This is an interdisciplinary and transdisciplinary approach that allows us to build bridges between science and religion. Research results. Drawing upon interdisciplinary and transdisciplinary connections, the author regards social philosophy of science as a contemporary trend that emphasizes the interpretation of the latest scientific achievements. Analyzing historical models of interaction between science and religion as cultural phenomena, three dominant types of relationship are identified: conflict, independence, and dialogue. The article outlines the main concepts used to characterize various models of interaction between science and religion. Discussion. Conceptual ideas of theophysics, fine-tuning of the Universe, intelligent design, the multiverse, and theology of science are analyzed for their potential in shaping the foundations of the modern world picture. The scientific novelty lies in the justification of a turn to the social philosophy of science, which enables the analysis of the science–religion relationship to evolve from conflict to dialogue. Conclusions. It is demonstrated that the creative conflict and independence in the relationship between science and religion has been replaced by an alternative of dialogue. Modern science faces fundamental issues that cannot be answered only by the scientific method. They are ontological and existential issues. The use of the approach of social philosophy of science and transdisciplinary methodology is proposed. Dialogue enables every field of human knowledge and culture to develop effectively, to respond to each other's achievements. It is argued that there are tendencies to form a new integrity of the worldview based on the convergence of the scientific and religious world picture.